Cost-Effectiveness Analysis of Abemaciclib Plus Fulvestrant in the Second-Line Treatment of Women With HR+/HER2– Advanced or Metastatic Breast Cancer: A US Payer Perspective - Wang, Yingcheng; Rui, Mingjun; Guan, Xin; Cao, Yingdan; Chen, Pingyu (Frontiers in Medicine, 2021)
Introduction: This study evaluated the cost-effectiveness of abemaciclib plus fulvestrant (ABE+FUL) versus palbociclib plus fulvestrant (PAL+FUL), ribociclib plus fulvestrant (RIB+FUL) and fulvestrant monotherapy (FUL) as second-line treatment for hormone receptor-positive and human epidermal growth factor receptor 2- negative advanced or metastatic breast cancer in the US. Methods: The 3 health states partitioned survival (PS) model was used over the lifetime. Effectiveness and safety data were derived from the MONARCH 2 trial, MONALEESA-3 trial and PALOMA-3 trial. The parametric survival models were used for four treatments to explore the long-term effect. Costs were derived from the pricing files of Medicare and Medicaid Services, and utility values were derived from published studies. Sensitivity analyses including one-way sensitivity analysis, probabilistic sensitivity analysis and scenario analysis were performed to observe model stability. Results: In the PS model, compared with PAL+FUL, ABE+FUL yielded 0.44 additional QALYs at an additional cost of $100,696 for an incremental cost-utility ratio (ICUR) of $229,039/QALY. Compared with RIB+FUL, ABE+FUL yielded 0.03 additional QALYs at an additional cost of $518 for an ICUR of $19,314/QALY. Compared with FUL, ABE+FUL yielded 0.68 additional QALYs at an additional cost of $260,584 for ICUR of $381,450/QALY. From the PS model, the ICUR was $270,576 /QALY (ABE+FUL vs. PAL+FUL), dominated (ABE+FUL vs. RIB+FUL) and $404,493/QALY (ABE+FUL vs. FUL) in scenario analysis. In the probabilistic sensitivity analysis, the probabilities that ABE+FUL were cost-effective versus PAL+FUL, RIB+FUL and FUL at thresholds of $50,000, $100,000 and $200,000 per QALY gained were 0% and the probabilities that ABE+FUL were cost-effective versus PAL+FUL and RIB+FUL at thresholds of $50,000, $100,000 and $200,000 per QALY gained were 0.2%, 0.6% and 7.3%. Conclusions: The findings from the present analysis suggest that ABE+FUL might be cost-effective compared with RIB+FUL and not cost-effective compared with PAL+FUL and FUL for second-line treatment of patients with HR+/HER2- advanced or metastatic breast cancer in the US.